TANTANGAN PERTAHANAN NASIONAL MENUJU INDONESIA EMAS 2045 - Ahmad Fanani; I Wayan Midhio; Afrizal Hendra (TheJournalish: Social and Government, 2024)
Golden Indonesia 2045 is a long-term vision launched to mark 100 years of Indonesian independence. This vision covers various aspects of development, including economic, social and defense. National defense policy is one of the key elements in ensuring the achievement of this vision, considering the importance of national stability and security as the foundation for sustainable development. This research aims to see the challenges in the aspect of national defense towards a golden Indonesia 2045 and the role of national defense in realizing a golden Indonesia 2045. The research method used is a literature study involving analysis of documents, books, journal articles and information from official websites. Indonesian national defense. The findings obtained by researchers in this research are that there are several challenges faced by Indonesian national defense such as Economic and Resource Challenges: Defense Budget Limitations and the Need for Military Modernization, Institutional and Bureaucratic Challenges: The Need for Reform of Defense Institutions and Bureaucracy and Budget Limitations and Priorities National: Balancing Economic Development and Defense Investment. Meanwhile, the role of national defense in realizing a Golden Indonesia 2045 is implementing Defense Diplomacy in the context of international cooperation in maintaining regional security and building national resilience and responding to non-conventional threats. Non-conventional threats such as terrorism, separatism, cyber attacks and climate change.